THREAT ACTORS SEEKING TO EXPLOIT AI CAPABILITIES. TYPES AND THEIR GOALS - KOVACI, Petru-Dan (Strategic Impact, 2024)
Artificial Intelligence’s advancement has led to ethical and privacy concerns due to the ability of algorithms to mine personal data and conduct surveillance on a large scale. The influence of Artificial Intelligence (AI) in cybersecurity extends beyond private entities and individuals. In this scenario, it is important to highlight the threatening actors and their objectives in order to counter AI-based cyber threats. We are dealing with different entities, each having its own interests: cybercriminals are interested in making profit, terrorist groups cause ideological violence and nation-states target geopolitical influence. Moreover, they are increasingly interested in developing AI-driven cyber warfare capabilities for either attacking their enemies or enhancing their defence measures against such attacks. This trend will most likely aggravate the global cyber arms race as countries compete to surpass each other in the development and deployment of AI-driven cyber capabilities. Consequently, it has become crucial for organizations and individuals to understand how AI affects cybersecurity and, thus, adapt their strategies accordingly. Traditional defences must be supplemented with AI-powered tools and techniques to stay ahead of the curve, while security experts must continually update their skills and expertise to cope with the changing threat landscape.